2015
DOI: 10.2527/jas.2014-8833
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid metabolism and β-adrenergic response of adipose tissues of periparturient dairy cows affected by an energy-dense diet and nicotinic acid supplementation1

Abstract: Dairy cattle will mobilize large amounts of body fat during early lactation as an effect of decreased lipogenesis and increased lipolysis. Regulation of lipid metabolism involves fatty acid synthesis from acetate and β-adrenergic-stimulated phosphorylation of hormone-sensitive lipase (HSL) and perilipin in adipocytes. Although basic mechanisms of mobilizing fat storage in transition cows are understood, we lack a sufficiently detailed understanding to declare the exact regulatory network of these in a broad ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 45 publications
5
19
0
Order By: Relevance
“…Milk yield and milk protein percentage were not affected by either RPN or free niacin supplement in early lactation in several studies (16,17,44,(46)(47)(48) , which is in line with most of the earlier studies investigating the effects of free niacin supplementation on milk yield and milk protein percentage (5) . Supplementation of RPN in early lactation decreased milk fat percentage in two studies (17,44) .…”
Section: Milk Yield and Compositionsupporting
confidence: 84%
See 3 more Smart Citations
“…Milk yield and milk protein percentage were not affected by either RPN or free niacin supplement in early lactation in several studies (16,17,44,(46)(47)(48) , which is in line with most of the earlier studies investigating the effects of free niacin supplementation on milk yield and milk protein percentage (5) . Supplementation of RPN in early lactation decreased milk fat percentage in two studies (17,44) .…”
Section: Milk Yield and Compositionsupporting
confidence: 84%
“…Those authors suggested that stimulating HCA 2 by nicotinic acid triggers the anti-lipolytic pathway. However, supplementing niacin in feed did not influence the HCA 2 mRNA abundance in the liver (16,17) or the extent of HSL phosphorylation in early lactation (48) . The short half-life of nicotinic acid or the ruminal degradation probably explains the lack of effect of niacin on HCA 2 mRNA abundance or HSL phosphorylation.…”
Section: Niacin Supplementation During Heat Stressmentioning
confidence: 82%
See 2 more Smart Citations
“…Nicotinic acid is hereby readily transformed into nicotinamide that is a precursor of the coenzymes β‐nicotinamide adenine dinucleotide (NAD + ) and nicotinamide adenine dinucleotide phosphate (NADP + ), which participate in anabolic and catabolic pathways. Niacin is well known for its anti‐lipolytic effect (Carlson, ), and nicotinic acid was shown in the bovine to downregulate lipolysis in vitro (Kenez, Locher, Rehage, Danicke, & Huber, ) while in vivo results are inconsistent showing either an anti‐lipolytic effect (Morey et al., ; Pires & Grummer, ; Yuan, Shaver, Bertics, Espineira, & Grummer, ) or no protective effects (Kenez et al., ; Tienken, Kersten, Frahm, Meyer, et al., ). Nicotinamide participates in the cellular energy metabolism and influences oxidative stress.…”
Section: Introductionmentioning
confidence: 99%